Tenure Politics and the Feminist Scholar - Arriola, Elvia R. (Columbia Journal of Gender and Law, 2003)
I begin my remarks here today by assuming that someone else in this symposium has affirmed the positive role played by the feminist law journal, as a material byproduct of the women’s movement in academia, in shaping the discipline of feminist legal theory, its methodology, visions, and goals. Yet, the symposium organizers asked us to consider whether there are obstacles that stand in the way of this significant role for the feminist review. I find it ironic that this question has been posed to someone like me who views herself as a wounded feminist scholar-wounded by the system of white male supremacy in legal education, but even more so wounded by my own past internalized attitudesi of resistance to my spirit2 as a critical Latina, lesbian, and feminist scholar. Let me explore some further assumptions embedded in the question of what exactly compromises the effectiveness of the feminist law journal. The symposium organizers have posed that question to those whom presumably are interested in publishing feminist research and preferably, though not exclusively, in feminist law journals. Initially, I asked myself whether this was a question of audience or mission. I will talk about the question of mission later. As a question of audience, however, I could not really see a problem. Presumably, those writing for the feminist law journal are probably also regular readers of feminist reviews. So, the editors of the journals should continue doing what they are doing. That is, unless the staff and resources of the journal are so compromised that they cannot produce quality work, or those desiring to publish feminist articles are themselves compromised b y other conflicting goals and n eeds that interfere with t he production of quality feminist writings. In which case we may have a problem.